2012
DOI: 10.1186/ar3693
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-34 produced by human fibroblast-like synovial cells in rheumatoid arthritis supports osteoclastogenesis

Abstract: IntroductionInterleukin-34 (IL-34) is a recently defined cytokine, showing a functional overlap with macrophage colony stimulating factor (M-CSF). This study was undertaken to address the expression of IL-34 in rheumatoid arthritis (RA) patients and to investigate its regulation and pathogenic role in RA.MethodsIL-34 levels were determined in the RA synovium, synovial fluid (SF) and fibroblast-like synovial cells (FLS) by immunohistochemistry, real-time PCR, enzyme-linked immunosorbent assay and immunoblotting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
107
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(117 citation statements)
references
References 44 publications
8
107
0
2
Order By: Relevance
“…Recently, it was reported that IL-34 was expressed in synovial tissues obtained from rheumatoid arthritis patients, and tumor necrosis factor α (TNFα) stimulated IL-34 expression in those synovial fibroblasts in culture (33,34). Giant cell tumors of bone have been shown to express IL-34 (17).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that IL-34 was expressed in synovial tissues obtained from rheumatoid arthritis patients, and tumor necrosis factor α (TNFα) stimulated IL-34 expression in those synovial fibroblasts in culture (33,34). Giant cell tumors of bone have been shown to express IL-34 (17).…”
Section: Discussionmentioning
confidence: 99%
“…However, circulating CSF-1 (Stanley 1979;Janowska-Wieczorek et al 1991) shows humoral regulation (Cecchini et al 1994;Pollard and Stanley 1996;Dai et al 2004). In contrast, IL-34 is not detectable in the circulation of healthy individuals (Hwang et al 2012;Tian et al 2013) and thus IL-34 actions are likely to be restricted to the local microenvironments in which they are expressed. Through their different spatiotemporal expression, the two ligands play complementary roles in regulating the development, maintenance, and activity of specific macrophage populations, Langerhans cells, neuronal progenitors (Wei et al 2010;Greter et al 2012;Nandi et al 2012;Wang et al 2012), as well as osteoclasts (Dai et al 2002) and Paneth cells (Huynh et al 2009) and the regulation of cells of the female reproductive tract (Wei et al 2010).…”
Section: Csf-1r Expressionmentioning
confidence: 99%
“…IL-6, induced by TNF-α, contributes to bone destruction by stimulating RANKL expression and by regulating development of Th17 lymphocytes [67]. TNF-α upregulates IL-34, which mediates chemotactic migration of OCPs and supports the RANKL-induced osteoclastogenesis in the absence of M-CSF [25].…”
Section: Effect Of Arthritic Mediators On Osteoclast Progenitorsmentioning
confidence: 99%
“…M-CSF induces the proliferation of OCPs, supports their survival and upregulates RANK expression [23,24]. IL-34, by binding to cFms, is able to replace M-CSF in RANKL-induced osteoclastogenesis [7,8,25].…”
Section: Differentiation Of Osteoclastsmentioning
confidence: 99%
See 1 more Smart Citation